The Effect Of Competency And Job Training On Employee Performance With Career Development As A Moderation Variable In Employees Medan Petisah Sub District Office - Susi Susi; Yohny Anwar (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to determine the direct influence of competency on employee performance, the effect of job training on employee performance and the effect of career development on employee performance. This study also looked at the indirect influence in the form of moderation on career development variables on the influence of competencies, job training and employee performance at the Medan Petisah District Office. This study is a quantitative research with descriptive analysis, the research sample consists of 50 respondents of ASN and Non-ASN employees of the Medan Petisah District Office. Data collection using questionnaires. The data analysis technique uses the SmartPLS 4.0 application. The results of the direct influence study showed that competence had a positive and significant effect on employee performance, job training had a positive and significant effect on employee performance and career development had a positive and significant effect on employee performance. The results of the research show that the indirect influence of career development is not able to moderate the relationship between competence and employee performance at the Medan Petisah District Office and career development is unable to moderate the relationship between job training and employee performance.